The last word : beyond the Bible wars to a new understanding of the authority of Scripture - Wright, N. T. (Nicholas Thomas) (New York : HarperSanFrancisco, 2005)
"In this succinct and significant book, N.T. Wright delivers a helpful lesson for our times on how to understand the place of scripture and the authority that the Bible can still hold in the midst of the religious confusion so prevalent today. His straightforward historical summary of the role of the Bible in public consciousness and in the church and his helpful suggestions for getting back on track make this book an unparalleled resource in this continuing discussion. Revealing how both evangelicals and liberals misread scripture, Wright shows the way we can restore the Bible to its rightful role as a guide for the church through its many controversies."--Jacket.
By whose authority? -- Israel and God's kingdom-people -- Scripture and Jesus -- The "Word of God" in the Apostolic Church -- The first sixteen centuries -- The challenge of the Enlightenment -- Misreadings of Scripture -- How to get back on track.
"Published in the United Kingdom as Scripture and the authority of God."
Keywords: Bible -- Evidences, authority, etc